The State of the Intestinal Microflora in Hospitalized Children with Acute Intestinal Infections - Z. M. Kuliyeva; L. I. Rustamova; S. M. Faradzheva; M. G. Aliev; I. B. Israfilbekova; M. N. Mamedova; S. F. Suleymanova; F. V. Gylyndzhova (Детские инфекции (Москва), 2018)
The purpose of this study was to study the state of the intestinal microflora in young children who received inpatient treatment for acute intestinal infections. A study of the microflora in 183 children aged 0 months. up to 3 years of life. At the same time, 43 (23.5%) children received breast milk, 53 (29.0%) were artificially fed and 87 (47.5%) mixed-fed children. All children were examined by bacteriological method. Conditionally pathogenic flora among hospitalized patients was detected in 114 (62.3%), Candida was mainly detected in 67.5% of cases, in 57 patients (50.0%) in association with other opportunistic microorganisms — Candida + St. aureus — in 32 (28.1%), Candida + P. vulgaris — in 9 (7.9%), Candida + + P. vulgaris + St. aureus — in 12 (10.5%), Candida + St. aureus + Ps. aeroginosa — in 4 (3.5%). As a result of studying the composition of the intestinal microflora in patients hospitalized with intestinal infection, a decrease in the number of E. coli and B. bifidum was found, 43.7% and 63.4%, respectively.